2012
DOI: 10.1002/cpp.1765
|View full text |Cite
|
Sign up to set email alerts
|

How to Define, Find and Classify Side Effects in Psychotherapy: From Unwanted Events to Adverse Treatment Reactions

Abstract: Recognition of adverse treatment effects is a characteristic of good therapists and treatments. Psychotherapists should be sensitive for negative effects. This can help improve the quality of treatment. The UE-ATR checklist can be used in psychotherapy trials, quality assurance, clinical practice and training of psychotherapists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
241
0
28

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(284 citation statements)
references
References 58 publications
5
241
0
28
Order By: Relevance
“…Our finding that around a third of patients dropped out of therapy is within the range of 20%-60% reported elsewhere (Reneses et al, 2009) and is 10% larger than reported rates where session 1 was excluded (e.g., RCP, 2011;2013). The mean therapist rate of 31.5% was similar to the 33.2% found by Zimmerman et al (2016), however, our therapist effect for dropout was twice that found in their study.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our finding that around a third of patients dropped out of therapy is within the range of 20%-60% reported elsewhere (Reneses et al, 2009) and is 10% larger than reported rates where session 1 was excluded (e.g., RCP, 2011;2013). The mean therapist rate of 31.5% was similar to the 33.2% found by Zimmerman et al (2016), however, our therapist effect for dropout was twice that found in their study.…”
Section: Discussionsupporting
confidence: 78%
“…In part this has been due to the absence of sufficiently large datasets to study therapist effects, but also to inconsistencies in the definitions of the range of negative outcomes. Linden (2013) classified negative outcomes, as different types of 'unwanted events', some of which are adverse reactions to the therapy, while others may or may not be therapy related. Two manifestations of the latter are unplanned endings, often termed dropout, and patient deterioration.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Linden recently proposed a theoretical framework for side effects of psychotherapy [55]. In his paper, Linden presents definitions of unwanted events, treatmentemergent reaction, adverse treatment reaction, malpractice reaction, treatment non-response, deterioration of illness, therapeutic risk, and contraindications.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…82,105,106 Specification of the nature of possible harms and identification of the type of person who may be susceptible to harm is important information to collect to establish risk-benefit balances that ought to be available to clinical services to inform the choice of treatments provided and to patients to help them make decisions about consenting to psychosocial treatment. Linden 107 has offered definitions of a range of unwanted events and adverse treatment reactions and has constructed a checklist for recording the existence, severity and treatment-relatedness of these events that may be of value for systematic observation of harms in clinical trials. Jonsson et al 105 offer suggestions for collecting and reporting adverse effects in RCTs, including providing a plan for how harms will be detected within the protocol for ethical review, using structured assessment methods such as checklists or rating scales, active and regular monitoring, and reporting the absence of harms as well as the occurrence of harms.…”
mentioning
confidence: 99%